Place still matters in the digital age: Neighbourhood social capital, online engagement, and mental health in China - Yang Xiao; Yihui Huang; Siyu Miao (Transactions in Planning and Urban Research, 2026)
Neighbourhood social capital has long been regarded as protective for mental health through everyday face-to-face interaction. At the same time, rapid digitalization is reshaping patterns of social connection in ways that may reorganize the distribution of these place-based protections and contribute to urban mental health inequalities. This study examines the associations between multidimensional digital engagement, neighbourhood social capital, and depressive symptoms in China, and assesses whether these relationships differ by gender and marital status. The analysis draws on 13,443 adults from the 2016 and 2020 waves of the China Family Panel Studies. Pooled cross-sectional ordinary least squares models with wave controls are estimated, followed by subgroup analyses stratified by gender and marital status. Neighbourhood social capital is consistently associated with lower levels of depressive symptoms after adjustment for socioeconomic characteristics and multiple dimensions of internet use, indicating that local social environments remain relevant under conditions of widespread connectivity. In contrast, the associations between digital engagement and depression vary by activity type. Internet use oriented toward maintaining contact with family and friends is associated with fewer depressive symptoms, whereas longer online time and work-oriented, business-oriented, and entertainment-oriented uses are more often associated with higher depressive symptoms. These patterns differ across social groups. The protective association of neighbourhood social capital is strongest and most consistent among married men. In contrast, internet-use-related correlates of depressive symptoms are generally more pronounced among women, especially married women, although the specific forms of internet use associated with depressive symptoms vary by marital status and across survey waves. The findings indicate that digital participation and neighbourhood social capital are jointly associated with depressive symptoms, but their associations are socially differentiated by gender and marital status. Strengthening neighbourhood-based social infrastructure remains central to reducing mental health inequalities in the digital era.